A Simulation on the Effect of Welding Sequences for T-joints under Single V Groove - Song, Lifei; Mao, Yunsheng; Xiang, Zuquan; Chen, Zhuo; Bin, Liu (Manufacturing Technology Journal, 2018)
T-joints are important structural components widely used in the shipbuilding and marine engineering; single V groove is the mostly used groove form for medium-thickness T-joints' welding due to its efficiency. However, because of the asymmetry, complex angular deformation is often produced during welding, which has a negative impact on the structural installation and strength. In this paper, SYSWELD software is used to simulate the welding deformation under single V groove of T-joint based on the thermo-elastic-plastic finite element method. The effectiveness of the model and simulation is verified by experimental results. On this basis, the influence of the welding sequences on the angular deformation is investigated and then the optimal scheme is analyzed. The results provide a theoretical guidance for the practical welding of T-joints in ships and marine engineering structures.
Keywords: Welding Sequence; Angular Distortion; T-joint; Single V Groove